The effect of cognitive stimulant strategy on my method (included, separate) and the performance of some basic football skills for students - Naser, Talib Mousa; Al-Saffah, Raghda Hamza (International Journal of Psychosocial Rehabilitation, 2020)
The educational process has witnessed a remarkable development from its traditional formulas to several patterns in the development of learners and the development of their mental abilities. More advanced teaching strategies have emerged than they were previously, and this in turn has helped the teacher and learners in bringing about a wide change in all scientific fields. As for the research problem, the researcher believes that the remarkable scientific progress in the accelerated educational system is intended to be matched and pursued by the teacher and learners together and through the use of stimulants of cognitive strategy and modern educational techniques compatible with this tremendous scientific progress. One of the objectives of the research • Knowing the effect of using cognitive stimulants strategy on the basis of my method included, separate and the strategy followed by the teacher in the College of Physical Education and Sports Science - the first stage - football • Knowing the effect of using cognitive stimulants strategy on the basis of my method included, separate, and the strategy followed by the teacher in performing some basic football skills for students. • Understanding the preference of influencing the use of cognitive stimulants strategy according to my method (included, separate) and the strategy followed by the teacher and performance of some basic skills of football for students. The research hypotheses were • There is a positive effect of the use of cognitive stimulants strategy on the basis of the included method and the separate method and the strategies followed by the teacher in improving the motivation of learning for students of the Faculty of Physical Education and Sports Science - the first stage by studying football. • There is a positive effect of the use of cognitive stimulants strategy, according to the method included, separate, and the method followed by the teacher in the performance of some basic football skills for students - Department of Physical Education and Sports Science. • There is an advantage in influencing the use of the cognitive stimulant strategy, according to the method involved and the separate method and the strategy followed by the teacher in performing some basic football skills for students. The researcher used the experimental approach to identify the effect of cognitive stimulant strategies in developing basic skills in football. The same sample was identified by Al-Mustansiriyah University students - College of Basic Education - Department of Physical Education and Sports Science and from the first stage for students and the curriculum lasted (10) weeks and the rate of educational unit for each week For three classs (ABC), the time of the educational unit was (90) minutes, and the researcher used a set of statistical methods to process the research data The researcher concluded the most important results • The review of the student’s cognitive stimulants by the teacher at the beginning of the main section of the educational unit had a significant and distinctive impact on the process of meditation, thinking, linking, deduction, and application of skills. • In the light of the results of the research, the researcher concluded that the use of cognitive strategy stimulants in teaching sports science and including them in their academic priorities has a profound impact on raising the level of students.